The Antitubercular Activities of Natural Products with Fused-Nitrogen-Containing Heterocycles - Helena I. Boshoff; Neha Malhotra; Clifton E. Barry; Sangmi Oh (MDPI AG, 2024)
Tuberculosis (TB) is notorious as the leading cause of death worldwide due to a single infectious entity and its causative agent, Mycobacterium tuberculosis (Mtb), has been able to evolve resistance to all existing drugs in the treatment arsenal complicating disease management programs. In drug discovery efforts, natural products are important starting points in generating novel scaffolds that have evolved to specifically bind to vulnerable targets not only in pathogens such as Mtb, but also in mammalian targets associated with human diseases. Structural diversity is one of the most attractive features of natural products. This review provides a summary of fused-nitrogen-containing heterocycles found in the natural products reported in the literature that are known to have antitubercular activities. The structurally targeted natural products discussed in this review could provide a revealing insight into novel chemical aspects with novel biological functions for TB drug discovery efforts.